Clinical study of various risk factors associated with intrauterine fetal death - K., Ashok Kumar; Kanakeri, Ravindra; Anjanappa, Bharathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The death of a fetus is one of the unhappy events in the field of obstetrics. It is really distressing when it occurs without warning in a pregnancy that has previously entirely normal. It is thus vital to identify specific probable causes of fetal death to determine the risk of recurrence, prevention or corrective action. Methods: A prospective observational study was conducted in ESIC MC and PGIMSR, Rajajinagar, Bangalore, Karnataka, India. All cases of intrauterine fetal death confirmed either with ultrasound or on clinical examination by absence of fetal heart rate and fetal movements were studied. The age, parity, literacy, socio-economic status was recorded. Detailed history, clinical examination, associated conditions. Mode of delivery and details of the fetus and their placentas were noted. They were followed for 3 days for complications. Results: Mean maternal age was 26.03yrs, 98.5% of the women were booked cases, 82% belonged to lower middle class.16.39% of the women had hypertensive disorder of pregnancy, 4.91% had gestational diabetes, 9.8% had abruption placentae, 9.8% had oligohydramnios and 1.63% had polyhydramnios 4.9% were Rh isoimmunisation, 1.9% had twin pregnancy, 3.27% had PROM, 6.6% had cord accidents, 21% had anomalous fetus, 3.27% foetuses had non immune hydrops, 19.67% of IUDs were unexplained. Conclusions: Unexplained causes, PIH and abruptio placentae were major causes of IUFD. Significant proportion of IUFD due to PIH and abruption placenta is preventable by regular antenatal care and timely intervention. Despite advances in diagnostic and therapeutic modalities large number of fetal deaths remain unexplained. Poverty, illiteracy, unawareness and inaccessibility may be some of the reasons for unexplained IUFD.